2017
DOI: 10.5489/cuaj.4769
|View full text |Cite
|
Sign up to set email alerts
|

Management of advanced kidney cancer: Canadian Kidney Cancer Forum (CKCF) consensus update 2017

Abstract: N/A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 90 publications
0
15
0
Order By: Relevance
“…The death rate observed in our study was similar to that observed by Fall et al in Senegal with a mortality rate of 47%. [6] All genitourinary cancers, kidney cancer, in particular renal cell carcinoma (RCC), shows the rate of mortality highest [4]. These observations only confirm the derogatory nature of kidney cancer, which is considered to be the most lethal cancer in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The death rate observed in our study was similar to that observed by Fall et al in Senegal with a mortality rate of 47%. [6] All genitourinary cancers, kidney cancer, in particular renal cell carcinoma (RCC), shows the rate of mortality highest [4]. These observations only confirm the derogatory nature of kidney cancer, which is considered to be the most lethal cancer in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutically, radical or partial nephrectomy remains the standard treatment for renal cancer in adults in the localized stage. However, over the last ten years, significant therapeutic advances in the management of kidney cancer have been noted with the development of ablative treatments, partial nephrectomy and especially with the use of targeted therapies in locally advanced and metastatic forms [4]. The objective of this work was to study the epidemiological, diagnostic and therapeutic aspects of kidney tumors in adults over the past 5 years in our center.…”
Section: Introductionmentioning
confidence: 99%
“…51 Although mRCC has entered the immune checkpoint inhibitor era, the set of six IMDC criteria (hemoglobin less than the lower limit of normal, corrected calcium greater than the upper limit of normal (ULN), platelets greater than the ULN, neutrophils greater than the ULN, Karnofsky performance status less than 80%, and time from diagnosis to treatment of less than one year) remains the recommended tool for patient counselling, treatment selection (e.g., initial observation, systemic therapy, cytoreductive nephrectomy), and future research studies. These IMDC criteria stratify patients with mRCC into 3 risk groups based on their score: favorable (0), intermediate (1-2), or poor (3)(4)(5)(6). It should be emphasized that the IMDC classification is a prognostic classification and not a predictive tool.…”
Section: Risk-stratificationmentioning
confidence: 99%
“…For more than a decade, targeted systemic therapies have been the standard of care for metastatic renal cell carcinoma (mRCC) and their use has been refined over time as clinical experience has evolved. [1][2][3][4][5][6] The 2019 consensus statement by the Kidney Cancer Research Network of Canada (KCRNC) introduced the role of immunotherapy as first-line systemic therapy for mRCC, either as doublet immunotherapy or in combination with a vascular endothelial growth factor receptor tyrosine kinase inhibitor (VEGFR-TKI), based on phase 3 studies that demonstrated improved survival compared to single-agent VEGFR-TKI (sunitinib). [7][8][9] Subsequently, there have been updates on two of the important previously report-ed phase 3 studies (CheckMate 214 and Keynote-426) that have reinforced prior results.…”
Section: Introductionmentioning
confidence: 99%
“…Cytoreductive “debulking” surgery has long been considered a standard of care for eligible patients with metastatic renal cell carcinoma and is still widely recommended for selected patients 1,2 . This recommandation relies on many retrospective data and on two prospective clinical trials showing an improved overall survival in patients undergoing nephrectomy before receiving Interferon therapy 3,4 .…”
Section: Introductionmentioning
confidence: 99%